Students’ Comprehension of the Greek Economic Crisis through an Introductory Macroeconomics Course - Marangos, John; Triarchi, Eirini (Panoeconomicus, 2022)
The purpose of the paper is to report on the effectiveness of macroeconomic courses in informing and educating Greek students during an actual economic crisis. To achieve this end, we rely upon an introductory macroeconomics course that focuses upon the severe Global Financial Crisis that got underway in 2008. We conducted a survey for examining how well Greek students understood the effects of this deep and prolonged crisis. What is innovative about our testing is that we undertook a statistical evaluation of responses of two cohorts of students drawn from Spring, 2014 and 2015 – as the crisis intensified from one year to the next. To the very best of our knowledge, such an exercise had not yet been attempted; namely, of measuring students’ comprehension of a crisis and comparing the valuations of two cohorts of students as this particular crisis grew increasingly severe. Our findings suggest that students were confident that they achieved a comprehensive understanding of the variables underlying the Greek Economic Crisis. As the crisis escalated, students place increased importance on their university as a main source of information that influenced and helped in forming their perceptions of the economic crisis. However, our findings suggest that the university courses did not serve as their primary source of their information. In conclusion, the crisis helps to exposed gaps in the undergraduate curriculum that could be remedied through bringing in a better selection of up-to-date class materials. Keywords: Greek economic crisis, Student’s comprehension, Introductory macroeconomics, Teaching macroeconomics, Global financial crisis. JEL: A22.